Randomised, double blind controlled trial on preoperative anxiety level between premedicated and nonpremedicated patients undergoing elective surgery - Vellan, Sinnathamby (2008)
Patients should not suffer needless anxiety before surgery. This study was aimed to determine the level of anxiety that exist in patients undergoing elective surgical procedure from various departments. Comparison was also made within the various demographical data obtained with specific objective. Methods: This was a prospective randomized, double blind controlled clinical trial on preoperative anxiety levels. Patients completed the anxiety assessment scales both before and after intervention. The scale used was Hospital Anxiety and Depression Scale(HADS) The fourteen questions were subdivided to assess anxiety and depression separately. Paired T-test within groups and independent T-test for between groups were used during statistical analysis using SPSS 11.0. A p < 0.05 was considered to be significant. Results: One hundred and forty scale sets were obtained with no statistically significant difference in demographic characteristic. The interventional group had preintervention mean anxiety score of 8.3 ± 2.3 (mean± SD) and post- intervention mean anxiety score of 3.3 ± 1.8 with p = 0.000 where the placebo group had preintervention score of 8.9 ± 2.3 and post-intervention score of 10.24 ± 2.9 with p = 0.001. Differences were also seen in mean anxiety score with ethnicity, gender, ASA class (American Society of Anesthesiologist) and type of operation. xiv Conclusion: In this study, it was found that significant level of anxiety existed preoperatively and premedication reduced it's level significantly. The placebo group had the highest level of anxiety and its level increased even more immediately before surgery. In addition, female patient, ASA II and patients undergoing gynaecological surgery had higher level of anxiety.